EFFECT OF FORENSIC ACCOUNTING SKILLS ON FINANCIAL REPORTING QUALITY OF NIGERIAN DEPOSIT MONEY BANKS - Muhammad, Rabi’u Ya’u; Abubakar, Shehu; Lawal, Muhammad Inuwa (Kashere Journal of Management Sciences, 2024)
The main objective of this study is to empirically examine the application of forensic accounting skills in improving financial reporting quality of Nigerian Deposit Money Banks. The study employed a survey research design and the population of the study consists of all the Nigerian deposit money Banks listed on the floor of the Nigerian Exchange Group as at 31st December, 2020. The study used primary sources of data collection through survey instrument in which ninety-eight (98) copies of questionnaire were administered to respondents drawn from Nigerian deposit money banks. The study variables consist of financial reporting quality as dependent variable and forensic accounting skills proxied by fraud prevention detection and deterrence skills, forensic audit, investigation and interviewing skills, litigation mediation and arbitration skills, and computer assisted review and audit review represent the independent variables. The data was analyzed using PATH analysis via Smart-PLS software. The result of the analysis revealed that all forensic accounting skills but one - fraud prevention, detection and deterrence skills, forensic audit investigation and interviewing skills, litigation mediation and arbitration skills have positive and significant influence on financial reporting quality. Lastly computer assisted review and audit review has no significant effect on financial reporting quality. Therefore, it is recommended that internal audit staff should regularly undergo training and development programs to acquaint them with relevant knowledge and skills for effective forensic auditing